STUDY OF THE EFFECT OF IGNITION ENERGY ON COAL DUST EXPLOSION OF SIZE 53-44?m IN LABORATORY - Hadi Putra, Septian
One of the dangers of underground mining is a coal dust explosion. There are five main components causing the coal dust explosion namely oxygen, fuel (coal dust), heat sources, dispersion and confinement. This study aims to analyze the effect of ignitor energy on the pressure value , the rate of pressure rise and the effect of the ignitor energy on MEC (Minimum Explosibility Concentration) value by using a USBM 20-L Chamber. The ignitor used in this study has an energy of 4.19, 6.28 and 8.38 kJ. The results of this study stated that the higher the ignitor energy, the greater the explosive pressure value. But with the higher concentration, the explosive pressure value will go to the same value for the same dust concentration using different igniton energy. The effect of ignitor energy on the rate of pressure rise is the higher the ignitor energy, the rate of pressure rise will be even greater. For MEC values close to PR values equal to 2 for tests with ignitor energies of 4.19, 6.28 and 8.38 kJ are 100 g/m3, 100 g/m3 and 50 g/m3. From this result, the relationship between ignitor energy and MEC value is the higher the ignitor energy, the MEC value will be smaller. This is in accordance with previous studies that have been conducted, namely the research of Chawla et al. (1995), Cashdollar et al. (1992) and Yuan et al. (2012).Furthermore,this study has a bigger MEC value than the study of Chawla et al. (1995), Cashdollar et al. (1992) and Yuan et al. (2012) because the coal used in this study has a lower calorific value than the comparative study.